IMPLEMENTASI UPAYA HUKUM DALAM PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK - Stefani, Inggrid; PA, Barata Putra; Tualangi, Louis Hebron; Hafizhah, Annisa; Rohan, Rosmalinda (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
The purpose of this research is to find out what efforts are being made by the government to prevent sexual violence against children, understand the existence of legal protection and know what roles can be played by parents and the environment. This study uses normative legal research methods using legal, conceptual and analytical approaches. Documentary research techniques are used in legal material collection techniques, while qualitative analysis methods are used in research analysis methods. The results of this study indicate that the government's role in preventing sexual violence against children is by imposing strict sanctions and giving appropriate punishments, creating a fan base, conducting cyber patrols and combating pornographic content in cyberspace. Regarding the existence of legal protection carried out by the government, namely in law no. 23 In 2002, regarding child protection, the government took steps to implement the TPKS Law and Law no. 39/1999 on human rights. Sex education can be carried out in the role of parents and the environment, while other efforts are made by the Indonesian government, namely the Indonesian government in collaboration with the Ending Child Sexual Exploitation (ECPAT) program in decision-making and solving cases of commercial sexual exploitation of children (ESKA).